The use of intraoral camera in the assessment of students requirement (work) - Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon; Mustafa Al-Ahmad, Basma Ezzat (EuroJournals Publishing, Inc., 2012)
The dental intra-oral camera has made a significant input in dental treatment .it allows the dentist and the patient to get a close-up look at areas of special interest in the patient's mouth.( As a dental friend once remarked... "to see is to know... to not see is to guess"). When we can "see “a defect filling on a monitor it becomes apparent what needs to be done. It then expanded in almost to be use in several clinical specialties (Haak.R2000). The biggest hurdle is patient’s acceptance treatment is that they often do not understand the dental condition affecting them. With an intraoral digital camera, patient education is simplified by being able to help the patient see what the dental professional see (Erten H, 2006). Newer intraoral cameras have USB connections, making them portable and easy to link to your existing network. With bright LED or halogen light sources, these intraoral digital cameras also allow to visualize more, helping you to diagnose carious tooth or fractured fillings which the naked eye may be mistake with, by the introduction of Intraoral cameras this is now totally possible. Dental and gingival conditions can be shown and the available dental treatment alternatives can be discussed. The bottom line is extra and intra-oral imaging is... patient can see what doctor sees". There is nothing better than having both the doctor and the patient on the same page and understand what needs to be done. These photographs help you make an informed decision on how you would like to proceed with your dental treatment. The intraoral camera is basically a video camera that can be placed in mouth is approximately the size of the dental handpiece. or dental mirror and has a light built in to the camera which illuminates the area to be examined. This camera has the ability to take a video or a series of still photographs of the area, allows displaying images on a computer monitor. The images can be saved and discussed with the patient. This exciting technology provides the knowledge needed to make important dental decisions. Patient can now participate in his own dental care; no more hidden treatment and no unknowns to deal with during dental visits. It needs an advanced and expensive technological devices and software that enables the supervisor to have a precise method of evaluation that is repeatable and applicable in different type of work and in different fields of dentistry, In addition to that, a skillful well trained staff is needed in the The Use of Intraoral Camera in the Assessment of Students Requirement (Work) 490 clinic at the time of work, whereas in this proposed project the assessment is repeatable, and could be re-evaluated again at any time and at any step of the work and by any other supervisor. In the past twenty years, most of the major technological breakthroughs in electronics have really been part of one larger breakthrough, which is converting conventional analog information (represented by a fluctuating wave) into digital information (represented by ones and zeros, or bits). This fundamental shift in technology totally changed how we handle visual and audio information; it completely redefined what is possible. The digital camera is one of the most remarkable instances of this shift because it is so truly different from its predecessor. Conventional cameras depend entirely on chemical and mechanical processes. On the other hand, all digital cameras have a built-in computer, and all of them record images electronically. Intraoral camera converts the image to the language that computers recognize bits and bytes. Essentially, a digital image is just a long string of 1s and 0s that represent all the tiny colored dots or pixels that collectively make up the image.